Kinetics Study of Yttrium Leaching from Zircon Tailings Using Sulfuric Acid - Harry Supriadi; Iga Trisnawati; Tri Handini; Sri Rinanti Susilowati; Vincent Sutresno Hadi Sujoto; Panut Mulyono; Himawan Tri Bayu Murti Petrus (Indonesian Journal of Chemistry, 2023)
From the analysis of zircon tailings using X-Ray Fluorescence (XRF), Yttrium is a rare earth element (REE) with the highest concentration compared to other REEs. The purpose of this study is to determine the best kinetic model for describing how sulfuric acid extracts Yttrium from zircon tailings. Leaching temperatures of 200, 250, and 300 °C were used to determine the kinetics. Samples were obtained at 0, 20, 40, 60, 80, 100, and 120 min for each temperature. This study discovered that the chemical reaction model's kinetics are the most closely related to those of the leaching process. The evaluation of the model utilizing the coefficient of determination (R2) on the relationship between each model and time lends support to this conclusion. The activation energy (Ea) of the leaching process is determined by the Arrhenius plot between ln k and 1/T. In the Yttrium leaching procedure, the Ea value is 14.42 kJ/mol. The chemical reaction model was in charge of the leaching process, according to the Ea value. The premise of the chemical reaction model is that chemical reactions regulate the rate of the reaction.